(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Employee motivation remains a critical challenge for organizations operating in highly competitive service industries, particularly within the financial leasing sector, where employees are required to achieve demanding performance targets while maintaining high-quality customer service. In this context, leadership practices play an essential role in shaping employees' work experiences and sustaining their motivation. This study aims to explore leadership practices employed by branch managers in improving employee motivation within Company X, an Indonesian financial leasing company. A qualitative case study approach was adopted to obtain an in-depth understanding of leadership practices as experienced by organizational members. Data were collected through semi-structured in-depth interviews and non-participant observations involving purposively selected participants with direct experience of the organization's leadership processes. The collected data were analyzed using thematic analysis to identify recurring patterns and meaningful themes emerging from participants' experiences. The findings revealed four major leadership practices that contributed to employee motivation: open and supportive communication, recognition and appreciation, participative decision-making, and coaching for employee development. These practices were perceived by employees as creating a supportive work environment characterized by trust, collaboration, continuous learning, and meaningful interpersonal relationships. The study demonstrates that employee motivation is influenced not only by organizational policies or financial incentives but also by leaders' consistent managerial behaviors embedded in daily workplace interactions. The findings contribute to the growing literature on leadership practices by providing qualitative evidence from the Indonesian financial leasing industry, a context that has received limited scholarly attention. From a practical perspective, the study suggests that managers can strengthen employee motivation by fostering open communication, recognizing employee contributions, encouraging collaborative decision-making, and providing continuous developmental support. These findings offer valuable implications for leadership development in financial service organizations and other service-based industries operating in dynamic and competitive environments.